Creative Art Work Atisundara | Tabuh Kreasi Atisundara - Kadek Krisna Dwipa Diartama; Ni Made Arshiniwati; Ni Ketut Suryatini (GHURNITA: Jurnal Seni Karawitan, 2023)
In the process of forming this work, we get a touch of idea when we see a bird of paradise that is very beautiful and beautiful to look at, the beauty of its feathers and the combination of colors that produce a very beautiful harmonization when viewed. Then from there I got the idea to create a work of art based on a bird of paradise, and after looking for references to books and I got one word for the title of the work I will create, namely "ATISUNDARA". Atisundara means daat ayu, or listuayu which in Indonesian means beautiful, graceful and others that contain the word beautiful. And the beauty in question is the beauty of the bird of paradise which is very beautiful both from the feathers, tail and color. Then the idea is transformed into a work of Tabuh Kreasi by playing intertwined melodic patterns and added with flute playing patterns to produce harmony, besides that there are also melodic patterns both at the time of the singer or later, in the gendered section and others. This work uses four parts, namely the first part gineman, gegenderan, bapang, and also pengcet. And the medium of expression used is gamelan Gong Kebyar.